Co-inoculation of mycorrhizal fungi and plant growth-promoting rhizobacteria improve growth, biochemical and physiological attributes in Dracocephalum kotschyi Boiss. under water deficit stress - Gasemi, Saeid; Mahdavikia, Hassan; Rezaei-Chiyaneh, Esmaeil; Banaei-Asl, Farzad; Dolatabadian, Aria; Sadeghpour, Amir (PeerJ, 2023)
Background Because of swift climate change, drought is a primary environmental factor that substantially diminishes plant productivity. Furthermore, the increased use of chemical fertilizers has given rise to numerous environmental problems and health risks. Presently, there is a transition towards biofertilizers to enhance crops’ yield, encompassing medicinal and aromatic varieties. Methods This study aimed to explore the impacts of plant growth-promoting rhizobacteria (PGPR), both independently and in conjunction with arbuscular mycorrhizal fungi (AMF), on various morphological, physiological, and phytochemical characteristics of Dracocephalum kotschyi Boiss. This experimentation took place under different irrigation conditions. The irrigation schemes encompassed well watering (WW), mild water stress (MWS), and severe water stress (SWS). The study evaluated the effects of various biofertilizers, including AMF, PGPR, and the combined application of both AMF and PGPR (AMF + PGPR), compared to a control group where no biofertilizers were applied. Results The findings of the study revealed that under water-stress conditions, the dry yield and relative water content of D. kotschyi Boiss. experienced a decline. However, the application of AMF, PGPR, and AMF + PGPR led to an enhancement in dry yield and relative water content compared to the control group. Among the treatments, the co-application of AMF and PGPR in plants subjected to well watering (WW) exhibited the tallest growth (65 cm), the highest leaf count (187), and the most elevated chlorophyll a (0.59 mg g−1 fw) and b (0.24 mg g−1 fw) content. Regarding essential oil production, the maximum content (1.29%) and yield (0.13 g plant −1) were obtained from mild water stress (MWS) treatment. The co-application of AMF and PGPR resulted in the highest essential oil content and yield (1.31% and 0.15 g plant−1, respectively). The analysis of D. kotschyi Boiss. essential oil identified twenty-six compounds, with major constituents including geranyl acetate (11.4–18.88%), alpha-pinene (9.33–15.08%), Bis (2-Ethylhexyl) phthalate (8.43-12.8%), neral (6.80–9.32%), geranial (9.23–11.91%), and limonene (5.56–9.12%). Notably, the highest content of geranyl acetate, geranial, limonene, and alpha-pinene was observed in plants subjected to MWS treatment following AMF + PGPR application. Furthermore, the co-application of AMF, PGPR, and severe water stress (SWS) notably increased the total soluble sugar (TSS) and proline content. In conclusion, the results indicate that the combined application of AMF and PGPR can effectively enhance the quantity and quality of essential oil in D. kotschyi Boiss., particularly when the plants are exposed to water deficit stress conditions.
Keywords: Essential oil; Fertilisers; Irrigation regimes; Phytochemical; Soluble sugar